A prospective non-randomized controlled trial testing the effectiveness of psychotherapeutic inpatient treatment of Post-COVID-19 syndrome - study protocol - Koller, Katharina; Kastel-Hoffmann, Silke; Herold, Regina; Morawa, Eva; Lieb, Marietta; Krehbiel, Johannes; Hohberger, Bettina; Erim, Yesim (BMC Psychology, 2024)
Introduction: In addition to physical symptoms such as dyspnea, fatigue, post-exertional malaise, and pain, a subgroup of patients with Post-COVID-19 syndrome (Post-Acute Sequelae of COVID-19, PASC) suffers from mental illnesses such as anxiety, depression, and neurocognitive impairments. To date, there are no causal treatments available for PASC. While initial studies show that psychotherapy improves psychological symptoms, PASC-related fatigue, and psychosocial functioning, further research is needed to evaluate the effectiveness of psychotherapeutic treatment for PASC. Methods and analysis: This study presents a non-randomized controlled trial aimed at evaluating the effectiveness of a five-week multimodal inpatient psychosomatic treatment program for individuals experiencing PASC symptoms and comorbid mental illness. A total of 118 patients presented at the Post-COVID Center at the Universitätsklinikum Erlangen will be assigned to the intervention group receiving inpatient psychosomatic treatment or the control group receiving treatment as usual. The inclusion criteria for the intervention group are a diagnosis of PASC and at least one condition of mental distress and problems with coping with illness. The primary objective of the intervention is to reduce mental ailments, including depression and anxiety, as well as neurocognitive deficits, and to address PASC symptoms such as fatigue and pain. The core elements of the treatment are psychotherapy in individual and group settings, medical treatment, neurocognitive training, and physical therapy, adapted to the individual’s capacity and oriented towards the concept of pacing. After enrollment, participants will undergo a 6-month follow-up to assess long-term results and the sustainability of the intervention effects. Discussion: This study examines the effectiveness of inpatient psychotherapeutic treatment in PASC patients with comorbid mental illness in comparison with a control group based on treatment as usual. The results of the study can contribute to the development of evidence-based interventions to address the complex needs of patients with PASC and comorbid mental illness. Trial registration: German Clinical Trial Register (DRKS), retrospectively registered 15.02.2024 DRKSID DRKS00033562.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Coping with illness; COVID-19; Fatigue; Mental illness; Post-COVID syndrome; Psychotherapy